URGENSI DESTINASI WISATA EDUKASI DALAM MENDUKUNG PARIWISATA BERKELANJUTAN DI INDONESIA - Prasetyo, Hendi; Nararais, Detin (Kepariwisataan: Jurnal Ilmiah, 2023)
The abundant cultural, historical, and natural wealth make Indonesia a special country. Along with the existing wealth, the existing potential can be packaged into educational-based tourist destinations. This research was conducted to determine the urgency of educational tourism destinations supporting sustainable tourism in Indonesia. This research was conducted using qualitative methods with a descriptive approach. Data collection techniques are carried out using secondary data in the form of library research. The results obtained in this study indicate that the urgency of developing educational tourism destinations in Indonesia is very important. Indonesia has abundant cultural, historical, and natural wealth, so educational tourist destinations can be a means of introducing Indonesian culture, history, and natural beauty to both local and foreign tourists. Educational tourism can help achieve sustainable tourism by focusing on educational and learning aspects as well as promoting environmentally friendly activities and products. Therefore, the urgency of educational tourism destinations is very important and needs to be supported and developed properly.